Analysis of Flue Gas Emission Data from Fluidized Bed Combustion Using Self-Organizing Maps - Mika Liukkonen; Mikko Heikkinen; Eero Hälikkä; Teri Hiltunen; Yrjö Hiltunen (Applied Computational Intelligence and Soft Computing)
Efficient combustion of fuels with lower emissions levels has become a demanding task in modern power plants, and new tools are needed to diagnose their energy production. The goals of the study were to find dependencies between process variables and the concentrations of gaseous emission components and to create multivariate nonlinear models describing their formation in the process. First, a generic process model was created by using a self-organizing map, which was clustered with the k-means algorithm to create subsets representing the different states of the process. Characteristically, these process states may include high- and low- load situations and transition states where the load is increased or decreased. Then emission models were constructed for both the entire process and for the process state of high boiler load. The main conclusion is that the methodology used is able to reveal such phenomena that occur within the process states and that could otherwise be difficult to observe.